New NMR methods and their applications in mechanistic studies - Wei, Ran (The University of Edinburgh, 2023)
Tracing the fate of fast irreversible chemical reactions remains a challenging and intriguing task in chemistry. While slow reactions can be monitored by routine NMR techniques at ease, real-time monitoring of fast reactions that are initiated by mixing, however, poses challenges to traditional NMR experiments and therefore requires specialised techniques. A state-of-theart stopped-flow piece of equipment was utilised in conjunction with a high-resolution NMR spectrometer, to enable the data collection of rapid reactions including identification of intermediates, side-products, and catalysts, and quantification of selectivity. This work consists of three main aspects regarding the stopped-flow technique: i) evaluating the physical parameters and functionalities of the stopped-flow instrument; ii) monitoring rapid irreversible reactions with half-lives shorter than seconds; and iii) exploiting the non-pre-magnetised input channel of the stopped-flow instrument for magnetisation transfer studies. Thus far, effective kinetic data collection for irreversible chemical reactions of half-lives in the order of milliseconds was achieved, with the aid of interleaved stopped-flow experiments. This was demonstrated by the base-catalysed protodeboronation of pentafluorophenyl boronic acid, of t1/2 = 45 milliseconds at 313 K. The functionality of the non-pre-magnetised stopped-flow input channel was experimentally validated by the chemical exchange studies without the necessity of isotopic labelling. In addition to the stopped-flow technique, a closely-related yet independent work on the measurements of longitudinal relaxation time constant (T1) was conducted. T1 is an important NMR parameter essential for quantitative NMR experiments and molecular dynamic studies. Therefore, prior to kinetic analysis, it is necessary to measure the T1 of spins in the system. Comparing to the most conventional approaches such as the ‘Inversion Recovery’ experiments, the methodologies developed in this work showed significant improvements in time efficiency and achieved sufficiently accurate T1 measurements. Furthermore, it was proved that continuous heteronuclear decoupling could be applied in T1 measurements, affording sensitivity enhancements from the removal of Jcouplings and the Nuclear Overhauser Effects. This application is particularly beneficial for insensitive nuclei, which intrinsically require longer experimental time. Throughout the developments of T1 methods with heteronuclear decoupling, a range of decoupling schemes were evaluated to highlight the appropriate choice for different spin systems.
Keywords: NMR; mechanistic studies